Paraffin crystallization process under the influence of magnetic field - Othman, Ariff; Abdul Kadir, Abdul Aziz (Universiti Teknologi Malaysia, 2000)
In the pipeline transportation of fluids, a common concern is the accumulation of impurities, contaminants, or constituents on the inner walls of pipelines from crude, unprocessed fluids such as crude oil or other similar petroleum products. For example, paraffin or wax is a constituent or component of crude oil, which has the tendency to collect on the internal surfaces of piping and pipelines. Accumulations of such constituents can rise to a level where a pipeline would be inoperable due to the congestion. The pipeline flow has to be interrupted to insert a "pig," or for applying hot oil treatment or other pipeline servicing device or method is used to clear the blockage. Furthermore, the paraffin hardens, adding additional wear to such servicing devices such as pigs. Such servicing operations typically take several hours and are time consuming and expensive.